11% Efficient Ternary Organic Solar Cells with High Composition Tolerance via Integrated Near‐IR Sensitization and Interface Engineering. Issue 37 (14th July 2016) - Nian, Li; Gao, Ke; Liu, Feng; Kan, Yuanyuan; Jiang, Xiaofang; Liu, Linlin; Xie, Zengqi; Peng, Xiaobin; Russell, Thomas P.; Ma, Yuguang
Abstract : Highly efficient electron extraction is achieved by using a photoconductive cathode interlayer in inverted ternary organic solar cells (OSCs) where a near‐IR absorbing porphyrin molecule is used as the sensitizer. The OSCs show improved device performance when the ratio of the two donors varies in a large region and a maximum power conversion efficiency up to 11.03% is demonstrated.